Investigating the usefulness of TikTok as an educational tool / Nur Ilianis Adnan, Syahirah Ramli and Isma Noornisa Ismail - Adnan, Nur Ilianis; Ramli, Syahirah; Ismail, Isma Noornisa (Universiti Teknologi MARA, 2021)
Living in a modem world requires educators to acquire skills in integrating technology into classroom activities to make the lessons more viable and fun for our generation Y and Z. There are a variety of new applications which can be used by educators as educational tools. This research aims to investigate the usefulness of TikTok as an educational tool and to gather students' feedback after using the TikTok application in their listening comprehension. The overall response to the survey was promising as most of the respondents gave positive feedback on the use of this application in their language learning process. Thus, the insights provided by this study on the usefulness of TikTok can be a guide for educators as well as policymakers aiming at exploring new educational tools to ease the teaching and learning process.